The Potential Threat of U.S. Intervention in Indonesia as a Consequence of the South China Sea Conflict: A Case Study of Indonesia’s Maritime Security - Pratondo Ario Seno Sudiro; Ahmad Syairofi Attabiq (Budi Luhur Journal of Strategic & Global Studies, 2026)
Abstract: The South China Sea conflict implies the return of the Cold War era with the upheaval between two major powers, there are the United States (US) and China. Unlike the Cold War, which was driven by ideological battles, the South China Sea Conflict is driven by geopolitical and economic battles. China is experiencing rapid economic growth with its ability to control trade routes in the South China Sea. This disturbed the US as an old power in the Asia Pacific region. Then, the conflict escalated with the construction of military bases along the South China Sea region to Indonesia. China itself has dared to submit the Nine Dash Line claim over 90% of the South China Sea area followed by the construction of military bases, two of them in Subi Reef and Fiery Cross Reef.The impact is the US feels threatened because international shipping lanes in the South China Sea will be fully controlled by China. This article aims to discuss US retention of China's increasing power in the South China Sea which has the potential to become a trigger for US intervention in Indonesia as an effort to counteract the pace of development of China's power. In preparing this article, a descriptive qualitative method based on literature studies was used. The data used in the preparation of this article is literature data derived from three kinds of sources, there are scientific articles, textbooks, and news articles or mass media. This study identifies indications and potential pathways of US strategic penetration which in the future has the potential to invite Chinese resistance so as to make Indonesia a new conflict field between the US and China. Abstrak: Konflik Laut China Selatan menyiratkan akan kembalinya era Perang Dingin dengan adanya pergolakan antara dua kekuatan besar yakni Amerika Serikat (AS) dan China. Berbeda dengan Perang Dingin yang dimotori oleh pertarungan ideologi, Konflik Laut China Selatan dimotori oleh pertarungan geopolitik dan pertarungan ekonomi. China mengalami pertumbuhan ekonomi yang sangat pesat dengan kemampuannya menguasai jalur perdagangan di Laut China Selatan. Hal itu mengusik AS sebagai kekuatan lama di kawasan Asia Pasifik. Akibatnya konflik meningkat dengan pembangunan pangkalan-pangkalan militer di sepanjang kawasan Laut China Selatan hingga mengarah ke wilayah Indonesia. China sendiri telah berani mengajukan klaim Nine Dash Line atas 90% wilayah Laut China Selatan yang diikuti dengan pembangunan pangkalan militer di Subi Reef dan Fiery Cross Reef. Akibatnya AS merasa terancam karena jalur pelayaran internasional di Laut China Selatan dapat dikuasai China sepenuhnya. Adapun artikel ini bertujuan membahas retensi AS terhadap peningkatan kekuatan China di Laut China Selatan yang berpotensi menjadi trigger bagi intervensi AS di Indonesia sebagai upaya menangkal laju perkembangan kekuatan China. Dalam penyusunan artikel ini digunakan metode kualitatif deskriptif yang berbasis studi literatur. Data yang digunakan dalam penyusunan artikel ini merupakan data literatur yang berasal dari tiga macam sumber yakni artikel ilmiah, buku teks, dan artikel berita atau media massa. Kemudian dilakukan koding dari data-data yang telah dikumpulkan dan disimpan, hingga diperoleh hasil bahwa terdapat ancaman intervensi AS di Indonesia yang dikemudian hari berpotensi mengundang resistensi China sehingga menjadikan Indonesia sebagai medan konflik baru antara AS dengan China.